Potential physiological tolerance mechanisms in faba bean to Orobanche spp. parasitism - Thebti, Siwar; Bouallegue, Amal; Rzigui, Touhami; En-Nahli, Youness; Horchani, Faouzi; Hosni, Taoufik; Kharrat, Mohamed; Amri, Moez; Abbes, Zouhaier (Frontiers in Plant Science, 2024)
Abstract Orobanche spp. are root parasitic plants that cause severe yield losses in faba bean (Vicia faba L.). The use of tolerant varieties remains as a pivotal component for a successful integrated control strategy. In this study, we investigated the potential physiological mechanisms associated with the tolerance to O. crenata and O. foetida in faba bean. Results showed that Orobanche parasitism significantly affected faba bean plants growth and seed production especially in the sensitive Bachaar (up to 61.77 % and 83.53% in shoot dry weight, up to 79.59% in pod number and no pod development when infected with O. foetida and O. crenata, respectively). This reduction was correlated to photosynthetic capacity (Amax) decreases in response to both O. foetida and O. crenata parasitism. This decrease was highly pronounced in the sensitive Bachaar with 24.57% and 63.43% respectively. Significant decreases were also observed in the sensitive Bachaar for the photochemical efficiency of PSII (Fv/Fm) (1.1% and 4.78%), the maximum transpiration (Emax) (11.8% and 39.13%) and the maximum water use efficiency (WUEmax) (24.97% and 41.77%) in response to O. foetida and O. crenata parasitism, respectively, against non-significant differences for the tolerant Chams, Chourouk and Zaher. The tolerant faba bean varieties were able to maintain a normal function of their photosynthesis capacity (An) and conserve their growth and seed production level, as a result of an acclimation to parasitic attack (Maintaining WUEmax). Our results suggest that yield components such as shoot dry weight, pod and leaf numbers and photosynthetic parameters notably the transpiration rate, can serve as suitable traits for assessing tolerance to Orobanche parasitism in faba bean plants.